Spinal cellular schwannoma: An analysis of imaging manifestation and clinicopathological findings. Issue 105 (August 2018) - Zhang, Enlong; Zhang, Jiahui; Lang, Ning; Yuan, Huishu
Highlights: Spinal cellular schwannomas were extremely rare. Imaging, clinical performances and pathology of spinal cellular schwannomas were retrospectively analyzed. Combining imaging with clinic and pathology to distinguish it from other tumors. Abstract: Objectives: Cellular schwannoma that occurs in the spine is relatively rare. Herein, we retrospectively analyzed the clinical and imaging data from nine cases of spinal cellular schwannoma. Materials and Methods: The clinical, imaging data and pathological manifestations were retrospectively analyzed from nine cases of pathologically confirmed spinal cellular schwannoma. Results: All nine cases were treated with surgical excision; seven cases were solitary lesions characterized by a dumbbell-shaped soft tissue mass growing out across the intervertebral foramen and two cases were multiple nodular lesions in the spinal canal. Six cases had compressive bony destruction, one case displayed osteolytic and compressive bony destruction, and two cases were without apparent bony destruction. Computed Tomography (CT)scans showed three cases were isodense and two cases were miscellany density. Magnetic Resonance Imaging (MRI) scans showed that the solid part of the tumor was isointense on the T1-weighted imaging (T1WI); five cases were isointense and three cases were slightly hyperintense on T2-weighted imaging (T2WI). Five cases exhibited hyperintense cystic regions. MRI enhanced scanning showed that 3/7 cases showed moderately to markedly heterogeneous enhancement and the remaining 4/7 cases showed markedly homogeneous enhancement. Except for one recurrence, 8/9 cases had a good prognosis. Conclusion: Spinal cellular schwannoma should be diagnosed combining the imaging manifestation with clinical performance and pathological examination in order to distinguish it from other tumors, such as classical schwannoma and malignant peripheral nerve sheath tumors.